Solving Course Timetable Problem by using Integer Linear Programming (Case Study IE Department of ITS) - Fakher Shwan Rafeek; Nurhadi Siswanto (Institut Teknologi Sepuluh Nopember, 2015)
Making IE department of ITS course timetable by determine the hard and soft constraints then develop an integer programming (ILP) model method to solve this NP-complete problem of Timetabling for solving Hard constraints Assignment problem and to solve the Soft constraints use Penalty Algorithm. Use LINGO software for solving suggested mathematical model to get the final results. Then do numerical analyzes for that results. Finally it achieves the goal for solving the Course Timetable. And get feasible solution of timetable as well as it gets the best required objective what it can get from the case study which is 356 events and it reduces the time of getting one timetable to be just one hour after it was at least 2 weeks.